LITIGATING CROSS-BORDER ENVIRONMENTAL DISPUTE IN INDONESIAN CIVIL COURT: THE MONTARA CASE - Prihandono, Iman; Dewanty R. K., Esty Hayu (Indonesia Law Review, 2015)
In August 2009, a wellhead blowout of took place at an offshore drilling facility named the Montara platform, on the north coast of Australia. This incident released crude oil into the sea and continued until November 2009. The Montara platform is owned by PTTEP Australasia Pty. Ltd., a company incorporated under the law of Australia, and a subsidiary of PTT Exploration and Production Public Company Limited, a Thailand based, state-owned oil company. Based on samples taken by the East Nusa Tenggara Municipality in the waters along the coast of Kolbano, it was found that the sea water has been polluted with crude oil. There was an indication that the crude oil was identical to those of at the Montara well head platform. This incident has been detrimental to at least 9.000 fishermen and seaweed farmers along the coast of West Timor Sea, with total losses estimated at USD2.4 billion. This article examines the possibility of a lawsuit brought by the affected communities to the Indonesian civil court. This article finds that filing a lawsuit against foreign entity may be possible. Article 100 RV of the Indonesian law on civil procedure provide an opportunity to sue foreign entity when a contractual relationship exists.